Crystallization and modelling studies of human oxydosqualene cyclase hOSC wild type and 580W mutant variant - Guger, Isabella (Jihočeská univerzita, 2019)
The aim of this study was to learn the basic and advanced crystallization techniques on the model protein Lysozyme, to crystalize the monotopic integral membrane protein human oxidosqualene cyclase hOSC-WT and its mutant variant hOSC-580W and to optimize the initial crystallization experiments. Moreover, the 3D hOSC protein structure was modelled and compared with already known structure of oxidosqualene cyclase.
Crystallization and modelling studies of human oxydosqualene cyclase hOSC wild type and 580W mutant variant